EDUCATION, SCHOOL AND ETHNIC-RACIAL RELATIONS: AN APPROACH TO THE CHILDREN'S AND YOUTH LITERATURE - Silva, Eva Aparecida da [UNESP] (Centro Ensino Superior Juiz De Fora, 2020)
When approaching children's literature, through the book Betina, by Nilma Lino Gomes, this article systematizes some reflections, based on bibliographic research, about the interlocution between education, school and ethnic-racial relations, highlighting the importance of positive representation of black subjects in children's and youth literary works, as we have a schooling of literature or schooled literature, just as it is also essential in textbooks. However, when emphasizing school education and the place of children's and youth literature in school, we reflect on the role of this type of literature in recognizing and valuing cultural diversity, in particular ethnicracial, in building self-esteem black children and adolescents, as well as a positive black identity. And for this construction, the positivization of the body and black aesthetics is of fundamental importance, especially curly hair and all the meanings attributed to it, as portrayed by Nilma Lino Gomes in her research and in the book Betina. Although this process should bring about changes in the relationships established between blacks and whites, through the re-education of racist attitudes and mentalities, as proposed by Law 10639/2003.
Keywords: Education; School; Children's and youth literature; Ethnic-racial relations